ACCOUNTING INFORMATION SYSTEM AND ORGANIZATIONAL PERFORMANCE: SPECIAL REFERENCE TO THE SERVICE SECTOR ORGANIZATIONS IN ANURADHAPURA DISTRICT - Rodrigo, W.S.L. (University of Jaffna, 2019)
This study intends to investigate the usefulness of Accounting Information System (AIS) for organizational performance. AIS plays a significant role in today's dynamic business environment. It is becoming increasingly necessary for all businesses to incorporate information technology to access and utilize reliable information during the decision-making process. AIS is related to collecting, storing, and disseminating data for planning, controlling, coordinating, analyzing, and decision making. Hence, AIS can be considered as an element to identify the performance of the organization. The objective of this paper is to examine the relationship between AIS and performance of the service sector organizations, which are located in Anuradhapura District. Accuracy, efficiency, and reliability were utilized as predictors grouped under AIS, whereas profitability, liquidity, and effectiveness were the outcome variables. To collect the data, the researcher used a structured questionnaire and convenience sampling method was executed to select participants. The Statistical Package for Social Science (SPSS) was used to analyze and examine the hypotheses. The results of the study indicated that the accounting information system and organizational performance have a positive relationship. According to the findings of the study, the researcher recommends that continuous improvement of AIS and practical application of AIS are of utmost importance to improve the bottom line.
Keywords: Accounting Information System; Effectiveness and Organizational Performance